An investigation of cardiac vagal tone over time and its relation to vigilance performance: a growth curve modeling approach - McGarry, Shannon P. D.; Neilson, Brittany N.; Brown, Noelle L.; Strong, Kaylin D.; Greenlee, Eric T.; Klein, Martina I.; Coyne, Joseph T. (Frontiers in Neuroergonomics, 2023)
Research over the last couple of decades has demonstrated a relationship between psychophysiological measures, specifically cardiac functions, and cognitive performance. Regulation of the cardiac system under parasympathetic control is commonly referred to as cardiac vagal tone and is associated with the regulation of cognitive and socioemotional states. The goal of the current study was to capture the dynamic relationship between cardiac vagal tone and performance in a vigilance task. We implemented a longitudinal growth curve modeling approach which unveiled a relationship between cardiac vagal tone and vigilance that was non-monotonic and dependent upon each person. The findings suggest that cardiac vagal tone may be a process-based physiological measure that further explains how the vigilance decrement manifests over time and differs across individuals. The current research contributes to our understanding of vigilance by taking into consideration individual differences in cardiac vagal tone changes that occur over the course of the vigilance task. 1 Introduction Heart rate variability (HRV) measures the time fluctuations between cardiac cycles. This fluctuation is influenced by both parasympathetic and sympathetic nervous system activity (Berntson et al., 1997). The parasympathetic nervous system controls autonomic, or involuntary functions when the body is at rest, like digestion, heart rate, and breathing, to name a few. This is in comparison to the sympathetic nervous system which, broadly speaking, controls the body's "fight or flight" response, as it mobilizes the body's response to environmental and psychological stressors. Both the parasympathetic and sympathetic nervous systems are a part